Acceleration of Heavy Ions by Ultrafast High-Peak-Power Lasers: Advances, Challenges, and Perspectives - Jan Badziak; Jarosław Domański (Photonics)
Laser-driven ion acceleration is a new, rapidly developing field of research and one of the important applications of ultrafast high-peak-power lasers. In this acceleration method, extremely strong electric fields, induced by an ultrafast laser in the plasma generated by the laser–target interaction, enable the acceleration of ions to relativistic velocities on picosecond time scales and at sub-millimetre distances. This opens the prospect of constructing a fundamentally new type of high-energy ion accelerator—less complex, more compact, and cheaper than the ion accelerators operating today. This paper briefly discusses the basic mechanisms of heavy ion acceleration driven by an ultrafast high-peak-power laser and summarises the advances in experimental and numerical studies of laser-driven heavy ion acceleration. The main challenges facing this research and the prospects for the application of laser-accelerated heavy ion beams are outlined.